Cantor’s Diagonal Argument:: An Extension to the Socialist Calculation Debate - Murphy, Robert Patrick (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2013)
The author argues that the mathematical solution to the problem of economic calculation under socialism, as proposed by Dickinson and others, in the sense that it could obtain the rational use of resources in the absence of private property is incorrect, because a planner socialist committee need to publish a list containing an uncountable infinite number of prices and, according to Cantor’s diagonal argument used by that this theory it is impossible to construct such a list. Thus, the Socialist economy is truly impossible.